APURINIC/APYRIMIDINIC ENDONUCLEASE REPAIR ACTIVITY OF MtbXthA REPAIR ENZYME IN MYCOBACTERIUM TUBERCULOSIS, THE CAUSATIVE AGENT OF TUBERCULOSIS - Abeldenov , S.K.; Ramankulov , E.M.; Saparbaev , M.K.; Khassenov , B.B. (Eurasian Journal of Applied Biotechnology, 2015)
Tuberculosis is one of the leading causes of mortality worldwide due to a bacterial infection, which is associated with the emergence of multi-drug resistant strains in recent years. DNA repair enzymes, particularly AP (apurinic/apyrimidinic (AP)) endonucleases play an important role in maintaining genomic stability of Mycobacterium tuberculosis, the causative agent of tuberculosis. AP endonucleases are key DNA repair enzymes that are involved in the removal of abasic sites. In case of DNA damage, specific DNA glycosylases remove the damaged bases and form the AP site. AP endonucleases form breaks in the phosphodiester bond at the AP site and cut the sugar-phosphate residue. In this work, activity of the AP endonuclease repair enzyme, MtbXthA was studied. Recombinant MtbXthA protein was cloned, expressed, and purified using standard methods of genetic engineering. It was established that the AP endonuclease activity of MtbXthA depends on the ions Mg2+ and Mn2+. Maximum AP endonuclease activity of MtbXthA was demonstrated at 37°C. It was noted that MtbXthA was very sensitive to ionic strength, since a 10-fold inhibition of the reaction was observed using 100 mM potassium chloride. Optimal pH for MtbXthA activity was slightly acidic (pH 6.0-6.5).